Effect of Entrepreneurial Literacy and Self Efficacy on Entrepreneurial Intention in Students - Ruslan Juliana Pardosi (Budapest International Research and Critics University, 2022)
This study aims to determine effect of entrepreneurial literacy and self efficacy on entrepreneurial intention in students. The type of research used in this research is quantitative research. The population in this study are the students of the Institut Agama Kristen Negeri Tarutung, Christian Education Management S-1 Study Program, Class of 2019, totaling 48 students. The sampling technique used is the saturated sample technique. The data collection technique used is by using a questionnaire. The scale used is a Likert scale with 5 alternative answers. The data analysis technique used is PLS-SEM method. The results show that entrepreneurial literacy has a positive and significant effect on entrepreneurial intention. Self efficacy has a positive and significant effect on entrepreneurial intention.